Migratory foreign body in the airway manifesting as recurrent cardio-respiratory arrest: A rare case report - V K Goyal; A Singh; R Nagar; S Singh (Wolters Kluwer Medknow Publications, 2016)
Foreign body aspiration in children commonly presents with coughing, dyspnea, wheezing, cyanosis and stridor. Our case presented with cardio-respiratory arrest (CRA), and was successfully revived, but suffered recurrent CRA, and finally betel nut was retrieved from the airway. Here clinical course of the patient favours migration of foreign body leading to recurrent cardio-respiratory arrest. Foreign body migration in airway is an unusual phenomenon, and its presentation as recurrent cardio-respiratory arrest is very rare.